2018
DOI: 10.1038/s41598-018-34166-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide shock reveals the immune function of indoleamine 2,3-dioxygenase 2 through the regulation of IL-6/stat3 signalling

Abstract: Indoleamine 2,3-dioxygenase 2 (Ido2) is a recently identified catalytic enzyme in the tryptophan-kynurenine pathway that is expressed primarily in monocytes and dendritic cells. To elucidate the biological role of Ido2 in immune function, we introduced lipopolysaccharide (LPS) endotoxin shock to Ido2 knockout (Ido2 KO) mice, which led to higher mortality than that in the wild type (WT) mice. LPS-treated Ido2 KO mice had increased production of inflammatory cytokines (including interleukin-6; IL-6) in serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…41,42 The signal on chromosome 8 relates to an area between IDO2 and TC1. Of potential relevance to NAFLD, both genes have roles in modulating inflammation with IDO2 inducible by lipopolysaccharide and contributing to immune function 43 while TC1 modulates NF-jB signalling. Further investigation of these variants is needed.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The signal on chromosome 8 relates to an area between IDO2 and TC1. Of potential relevance to NAFLD, both genes have roles in modulating inflammation with IDO2 inducible by lipopolysaccharide and contributing to immune function 43 while TC1 modulates NF-jB signalling. Further investigation of these variants is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a previous study (19) we reported a nuclear labeling for IDO1 in NSCLC. However, it is generally not known how these two molecules would act at nuclear level, but the observation that some tumors present a nuclear localization of both IDO1 and IDO2 may suggest a signaltransducing function (13,30), something already noted about IDO1 (31).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which IDO2 controls IMQ-induced dermatitis remains unclear. In our previous report, IDO2 was demonstrated to be important in the regulation of STAT3 signaling using a lipopolysaccharide-induced endotoxin shock model [ 40 ]. STAT3 participates in signaling downstream of multiple cytokines implicated in psoriasis, such as IL-6, IL-10, IL-20, IL-22, and IL-23, and may have a role in mediating the innate immune response in psoriatic epidermis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%